Product Sales Information System on Teak Wood Furniture “UD. Jati Setia” Web-Based Using the CodeIgniter Framework: Sistem Informasi Penjualan Produk Pada Meubel Kayu Jati “UD. Jati Setia” Berbasis Web Menggunakan Framework CodeIgniter - Ignes Rutama (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2023)
Computerized technology in a company is a necessity today. It has brought significant changes to the business world. So, UD Jati Setia, as a teak wood furniture company engaged in furniture, wishes to implement these advances in technology and information. Currently, the marketing and buying, and selling process that is carried out is still using conventional methods and has not implemented a computerized information technology system. Regarding product introduction among the wider community, the UD Jati Setia company is still not optimal. The operational activities are still manual using a note. Therefore, this causes the development of a company to be prolonged, and its efficiency is not optimal. This study created a web-based sales information system to maximize, simplify and save time in managing and promoting products and companies. A web-based sales information system uses the Waterfall application development method, while system testing uses the Black Box. This system can assist the owner in managing transactions and promotions among the wider community.